A desinstitucionalização de adolescentes no munícipio de Uruguaiana no ano de 2024: avaliação de políticas públicas e desafios de "ir além da medida" - (:unkn) unknown (Universidade Federal do Pampa, 2025)
The deinstitutionalization of adolescents in the municipality of Uruguaiana is the central theme of this master's dissertation. The objective is to analyze public policies aimed at adolescents under institutional care protection measures, especially those approaching adulthood when their protection measures end. The research initially focused on adolescents between the ages of 12 and 17 in the Uruguaiana institutional care service. Data analysis involved observation, interviews, interpretation, and transcription, using content analysis (with categories constructed based on the objectives). The second phase focused on professionals working in the protection network—the judiciary, the Public Prosecutor's Office, and the mayor—through qualitative research interpretation. The results showed that adolescents recognize the automatic termination of the measure at age 18, but share a lack of future goals and a feeling of loneliness. The protection network identifies the need to focus on those leaving care. It was possible to demonstrate that there are discrepancies between public policies and young people who have experienced institutional dismissal due to adulthood.
The deinstitutionalization of adolescents in the municipality of Uruguaiana in 2024: evaluation of public policies and challenges of "going beyond the measure"
Keywords: Politicas Públicas; Medida de proteção; Acolhimento institucional; Public Policies; Protection measure; Institutional care; CIENCIAS HUMANAS